Can our residents carry the weight of the obesity crisis? A mixed methods study. Issue 3 (May 2015) - Ibrahim, Halah; Awadhi, Aydah Al; Shaban, Sami; Nair, Satish Chandrasekhar
Summary Background Obesity is a worldwide problem and has reached epidemic proportions in the Middle East. Although physicians are in a unique position to counsel and treat their obese patients, little is known about healthcare provider management of obesity in this region of the world. The purpose of this study is to assess resident physician diagnosis and management of obese patients, and barriers to obesity management in the United Arab Emirates. Methods We conducted a retrospective medical records review of an internal medicine resident clinic in an academic medical centre in the UAE. A focus group was then held with a convenience sample of 20 Internal Medicine residents. Questions were aimed at understanding barriers to obesity diagnosis and management. Focus group discussions were analysed using qualitative thematic analysis. Results Of 155 patients seen in resident clinic in 2012 and 2013 (representing 766 patient encounters), 50 (32%) met the criteria for overweight, and 102 (66%) met the criteria for obesity. Despite the high prevalence, only 9% had documentation of BMI or obesity in their medical record. Six percent were offered diet or exercise advice, and 6% were referred to a dietician. Focus group results indicated residents had sufficient knowledge, but lacked training in obesity management and adequate time for counselling. Weight biases and feelings of incompetence may exist among our trainees. Conclusion Obesity is under-recognised and under-treated by our residents. The findings confirm that a significant gap exists between optimal obesity management recommendations and the current practices of our trainees.